Productivity, non-compliance and the minimum wage - Eliane El Badaoui; Frank A. Walsh (University College Dublin, UCD School of Economics, 2021)
Many informal firms in developing countries would not be viable if they were to comply with the minimum wage law. This means the authorities have an incentive to turn a blind eye to nonenforcement in a substantial share of firms. We also survey enforcement mechanisms for the minimum wage across developing countries and find that worker complaints are an important element in determining whether firms will be inspected for non-compliance or not. We develop a theoretical monopsony model which rationalises the stylised facts we observe. For a given minimum wage, the government can choose a level of enforcement and penalties for non-compliance such that employment will not fall for any optimising firm, irrespective of their productivity. Low productivity firm's optimal choice of employment and wage will be unaffected by the introduction of the minimum wage. High productivity firms comply so that wage and employment effects are non-negative for these firms.
Keywords: D24; J31; O17; 330; Minimum wage; productivity; non-compliance; informal sector; firms